STRATEGI PENDIDIKAN KEWIRAUSAHAAN PERGURUAN TINGGI (Studi empiris di Fakultas Teknologi Informasi dan Komunikasi Universitas Semarang) - Natalia Sari Pujiastuti (Universitas Semarang, 2020)
The implementation of the right strategy to implement Entrepreneurship Education is believed to be able to foster student entrepreneurial interest. Thus it is hoped that the Faculty of Information Technology and Communication Science, University of Semarang, as an important part of improving education and a place to produce quality people, needs to carry out entrepreneurial education strategically and comprehensively to support the government in reducing unemployment and producing technology-literate young entrepreneurs for the achievement of Indonesia. as a developed country in the year 2045.This study used a qualitative descriptive method based on the contribution of researchers as entrepreneurial activists and lecturers. From this study, it was found that the phenomenon of a lack of interest and entrepreneurial movement among students was revealed due to the lack of support from the tertiary education institution.